Methodology of insurance claims management in global practice - Iskandarov Abdurasul Mirjalil oglu, (THE INNOVATION ECONOMY, 2026)
This article explores the methodological foundations of managing insurance claims in global practice. It examines the processes of effectively resolving claims in the insurance market, international approaches, and the possibilities of adapting them to the context of Uzbekistan. Moreover, the role of innovative technologies and digitalization tools in claim management is analyzed. The findings provide practical methodological recommendations aimed at enhancing transparency, strengthening customer trust, and improving the operational efficiency of insurance companies in the national insurance system.